KOORDINASI OPERASIONAL DALAM LAYANAN F&B HOTEL: STUDI EMPIRIS PADA HOTEL IBIS MANADO CITY CENTER BOULEVARD - Bet El Silisna Lagarense; Agustinus Walansendow; Sony Wijanarko; Jeskrispen Lagarense (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2025)
This study aims to analyze operational coordination within the Food and Beverage (F&B) Service at the Ibis Manado City Center Boulevard Hotel Restaurant, focusing on the factors influencing effective staff coordination. The research addresses the responsibilities, duties, as well as the inhibiting and supporting factors affecting daily work coordination. The literature review covers theories on restaurants and their types, definitions of coordination, as well as the roles, skills, personality traits, and work motivation relevant to F&B Service personnel. A qualitative method was employed, using observation and documentation for data collection, and data analysis was conducted through data reduction, presentation, triangulation, and conclusion drawing. Findings reveal that inadequate coordination skills contribute to poor staff communication, negatively impacting professionalism in service operations. A case study at the hotel restaurant highlights coordination issues and identifies managerial aspects that require attention by F&B management. The study concludes that coordination skills are essential for enhancing professionalism and operational effectiveness. It is recommended that all F&B Service staff actively engage in continuous coordination to maintain effective communication and achieve shared organizational goals. Keywords: Coordination, Communication, Skills, Responsibility